IMPLEMENTASI KEBIJAKAN PENGUPAHAN DI KOTA TASIKMALAYA PASCA UNDANG-UNDANG CIPTA KERJA - Fariz Mulyana; Cicip Zemi Permadi; Novian Nurmanto (Berajah Journal, 2026)
This study aims to evaluate the implementation of wage policies in Tasikmalaya City following the enactment of the Job Creation Law and Government Regulation No. 51 of 2023. Using a qualitative method with a descriptive approach, this study identifies obstacles in enforcing the City Minimum Wage (UMK) standard. Data were collected through observation, in-depth interviews with purposively selected informants, and documentation. The analysis was conducted based on Marilee S. Grindle's policy implementation model, which includes policy content and implementation context variables. The findings show that the implementation of the wage policy has not been optimal due to disparities in interests among actors, limited human and financial resources, and low levels of compliance among business actors. The misalignment between wage formulation and the real cost of living has triggered resistance from worker groups, while the supervisory function of local governments remains co-opted by limitations in administrative authority.